Acid Production Potential of Lead-zinc Waste Rocks and Analysis of Heavy Metal Eluviating at Simulated Strong Acid Rain Environment - Yaohua CAO; Yongkang ZHANG; Hongzhao LIU; Wei WANG; Lin LIU (Kuangchan zonghe liyong)
This is an article in the field of ecological restoration of mines. A large amount of waste rock is inevitably produced in the process of mine development, and the release of heavy metal elements in the waste rock at the effect of weathering and eluviating will pose a threat to the water-and-soil quality around the mining area. In order to study the eluviating rule of heavy metal elements in lead-zinc waste rocks, the chemical composition and acid production potential of the waste rocks were analyzed. The leaching rates of heavy metal elements in the waste rocks and their mineral composition before and after eluviating were analyzed at simulated strong acid rain environment. The results showed that heavy metals elements of Cu, Pb, Zn, Cd, A sin the waste rocks had no independent minerals and were dispersed. The waste rocks had an ability of high acid neutralization, whose NAG was 0, with no acid production potential. In the eluviating tests at simulated strong acid rain environment, the pH values of leached solution were weakly alkaline, which was related to the waste rocks containing more alkaline minerals, and the waste rocks had a certain acid buffer capacity. The cumulative leaching rates of Cu, Pb, Zn, Cd and As increased with the leaching time in the first round. After the second round, the cumulative leaching rates of Cu, Pb, Zn and Cd tended to be stable, with almost nothing dissolved in the subsequent cycles. The cumulative leaching rates of As increased with the leaching time. In general, the leaching rates of heavy metals in the waste rocks were low. The mineral composition of the waste rocks was stable before and after leaching, and the mineral contents changed slightly. This article can provide a basis for the management of mine waste-rock dumps and the prevention and control of heavy metal pollution around them.